An Analysis Fighting Types of Onomatopoeia Words Found in “Superman The Doomsday Wars” Comic Written by Dan Jurgens - Arnadi, I Wayan Redi; Santika, I Dewa Ayu Devi Maharani; Pratiwi, Desak Putu Eka (Institut Pariwisata dan Bisnis Internasional, 2023)
People usually do imitation of an object such as animals, engine, or other object which produces sounds. This is to emphasizes the words, sentences, or utterances. It also helps to visualize the thing or object being discussed. This such imitation is called Onomatopoeia. This kind of word may appear in a written text, such as comic. This study aims to analyze the fighting type of onomatopoeic words in a comic entitled Superman: The Doomsday wars comic This study used theory that proposed by Elizabeth (2013) to identify the fighting types of Onomatopoeia found in Superman: The Doomsday wars comic. The data were collected by using observation method and note taking techniques. This study is a qualitative method and presented the analysis descriptively. The result of the study shows 29 data fighting types of onomatopoeia that found in Superman: The Doomsday Wars comic. This is because the story of this comic is about a battle between Superman and his Enemy, Doomsday.